Alpha-1 Antitrypsin is Markedly Decreased Following Pulmonary F. tularensis Challenge - Chambers, James P.; Yu, Jieh-Juen; Jupelli, Madhulika; Weintraub, Susan T.; Lopez-Ribot, Jose L.; Valdes, James J.; Arulanandam, Bernard P. (Frontiers in Cellular and Infection Microbiology, 2011)
Alpha-1 antitrypsin, a small glycoprotein clade A serpine serine protease inhibitor of neutrophil elastase has been shown to increase in humans following bacterial and viral infection. However, we report here significant reduction of this major inhibitor of elastase in plasma of F. tularensis LVS and SCHU S4 (Type A strain) following pulmonary challenge. Consistent with an imbalance of protease-antiprotease function at the alveolar level in lungs of infected animals, increased elastase activity was observed in lung lavage fluids accompanied by decrease lung function, i.e., loss of lung elastance with concomitant increase of pulmonary hysteresistivity. These data are suggestive of targeted tissue destruction via unchecked neutrophhil elastase activity in infected animals.